Training for community trauma assistance and reconciliation process - Ajduković, Dean (Array, 1998)
The logic model of training mental health providers to be able to respond to massive community trauma and to facilitate reconciliation in presented. The logic model is based on the major training effort in the region within which over 1,400 care-providers from over 90 communities and 130 organizations throughout Croatia and Bosnia Herzegovina were trained. This included psychologists (16%), social workers (19%), physicians and nurses (6%), special educators (3%), teachers (36%), graduate students (10%) and others. The trainees regularly serve over 120,000 beneficiaries. They were trained in: trauma psychology, community-based psychosocial interventions, innovative counseling techniques, prevention of burnout and vicarious traumatization, and implementation and evaluation of psychosocial services. Knowledge, skills and service indicators testified that the trainees demonstrated increased (1) understanding of the needs of trauma survivors; (2) awareness of consequences of massive traumatization for the communities; (3) appreciation of human rights issues; (4) availability of non-stigmatizing mental health services, and (5) emphasis on resilience factors and empowerment as a treatment approach. Many of the trainees were traumatized themselves or have suffered personal losses during the war. In some of the training groups the participants came from different ethnic groups to work on professional issues. The group and individual processes within that context were used to facilitate the bias awareness, reconstruction of the destroyed social fabric, facilitate re-association. The outcomes are discussed within framework of the steps of the logic model on the pathway to reconciliation, stability and peace and the role that professional training of a large number of mental health care-providers in a variety of communities can play.